Manipulation of Phototactic Responses by Two-Spotted Spider Mites to Improve Performance of Miticides - Christian Nansen; Patrice Jacob Savi; Tora Ward; Haleh Khodaverdi; Johann Heinrich Lieth; Anil V. Mantri (Crops)
Insight into phototactic responses by herbivorous crop pests may be used to manipulate their vertical distribution in crop canopies. Here, we tested the hypothesis that the deployment of specific light sources elicits positive or negative phototactic responses and can be used to enhance performance of miticide applications. We characterized movement responses by two-spotted spider mites (Tetranychus urticae) (spider mites) to seven light sources [ambient (control), UV-C, UV-B, blue, red, white, and near-infrared (NIR)] under experimental conditions. Separate experiments were conducted with/without the presence of a shelter. An analytical approach based on linear regression coefficients (intercept and slope) from observations in ascending order was used. Linear regression coefficients from UV-B indicated significantly negative phototactic bio-response. We examined settlement of spider mites when exposed to 11 light source configurations and with adaxial leaf sides facing either upwards or downwards. This experiment revealed strong positive and negative phototactic bio-responses to blue light and UV-B light, respectively. As a validation experiment, soybean plants were experimentally infested with spider mites and subjected to one of the following three treatments: (1) no treatment (control), (2) miticide [pyrethrins and Beauveria bassiana (BotaniGard Maxx)] only, and (3) a combination of blue and UV-B for 10 min immediately prior to miticide application. Integration of miticide application with prior deployment of blue and UV-B lights significantly increased the performance of miticide application. Results from this study supported the hypothesis. As a pest management approach, the integration of blue light (to elicit positive phototactic response) and UV-B (to elicit negative phototactic response) is believed to be of particular relevance to organic crop producers and/or to producers of crops for which limited numbers of miticides are registered.